Application of Social Worker Values and Ethics in Handling Neglected Children in Yogyakarta City - Muflihati, Abidah; Fiki, Rima Lea; Zakaria, Febiansyah; Rochmasani, Inafisah Luthfiah (UIN Sunan Kalijaga Yogyakarta, 2022)
This research aims to analyze the role of values and ethics in the practice of social workers in handling abandoned children in Yogyakarta City using a case study method. The research was conducted at the Social Service Office of Yogyakarta City, specifically in the Social Rehabilitation section that employs social workers, and at LKSA Wiloso Projo Yogyakarta. The research subjects include three social workers and three abandoned children under the care of LKSA Wiloso Projo. Data was collected through interviews, observations, and documentation. The study results indicate that social workers have implemented ethical values such as acceptance, confidentiality, accountability, non-judgmental attitude, objectivity, and self-determination. Acceptance helps create a more personal and comfortable relationship with the clients, while confidentiality protects the clients' privacy and maintains trust in interactions. Accountability and transparency are demonstrated at every intervention stage, ensuring that services adhere to applicable ethical standards. A non-judgmental attitude helps foster client openness, which is crucial in social rehabilitation. Objectivity ensures that interventions are carried out professionally without being influenced by personal biases. Meanwhile, self-determination respects the client's right to decide about their future. This research underscores the importance of applying values and ethics in social work practice, which enhances the quality of interventions and builds trust between social workers and clients. Thus, using these values significantly contributes to the success of social interventions and the well-being of abandoned children in Yogyakarta. Application of Social Worker Values and Ethics in Handling Neglected Children in Yogyakarta City Keywords: Values and Ethics in Social Work, Abandoned Children in Yogyakarta, Social Rehabilitation Practices Penelitian ini bertujuan untuk menganalisis peran nilai dan etika dalam praktik pekerja sosial dalam menangani anak terlantar di Kota Yogyakarta, dengan menggunakan metode kualitatif jenis studi kasus. Lokasi penelitian dilakukan di Dinas Sosial Kota Yogyakarta, khususnya di bagian Rehabilitasi Sosial yang memiliki pekerja sosial, serta di LKSA Wiloso Projo Yogyakarta. Subjek penelitian mencakup 3 pekerja sosial dan 3 anak terlantar di bawah perawatan LKSA Wiloso Projo. Data diperoleh melalui teknik wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan nilai-nilai etika seperti penerimaan, kerahasiaan, akuntabilitas, sikap tidak menghakimi, objektivitas, dan self-determination telah dijalankan dengan baik oleh pekerja sosial. Nilai penerimaan membantu menciptakan hubungan yang lebih personal dan nyaman dengan klien, sementara kerahasiaan melindungi privasi klien dan menjaga kepercayaan dalam interaksi. Akuntabilitas dan transparansi ditunjukkan dalam setiap tahap intervensi, memastikan bahwa layanan yang diberikan sesuai dengan standar etika yang berlaku. Sikap tidak menghakimi membantu membangun keterbukaan dari klien, yang sangat penting dalam proses rehabilitasi sosial. Objektivitas memastikan bahwa intervensi dilakukan secara profesional tanpa terpengaruh oleh prasangka pribadi. Sedangkan self-determination menghormati hak klien untuk mengambil keputusan terkait masa depan mereka. Penelitian ini menegaskan pentingnya penerapan nilai dan etika dalam praktik pekerjaan sosial, yang tidak hanya meningkatkan kualitas intervensi, tetapi juga membangun kepercayaan antara pekerja sosial dan klien. Dengan demikian, penerapan nilai-nilai ini berkontribusi signifikan dalam keberhasilan intervensi sosial dan kesejahteraan anak terlantar di Yogyakarta. Kata kunci: Nilai dan Etika Pekerjaan Sosial, Anak Terlantar di Yogyakarta, Praktik Rehabilitasi Sosial